Dementia Community Screening Program in District Health Area 11: Phase 1 - PHENWAN, Tharin; TAWANWONGSRI, Weeratian; KOOMHIN, Phanit; SAENGOW, Udomsak (Walailak Journal of Science and Technology (WJST), 2020)
To estimate the prevalence of dementia among Thai elderly in the upper Southern region of Thailand, we performed a cross-sectional screening of all Thai older people from 2 areas of Nakhon Si Thammarat province: Tambon Baan Thungchon, Tha Sala district, and Moo 6 and 7 from Sichon district, from December 2016 to November 2017. Trained health volunteers identified the participants in their communities and collected data including age, gender, comorbidities, Timed Up and Go Test (TUGT) results, and Montreal Cognitive Assessment (MoCA) scores. Our sample comprised 773 participants, of which 605 (78.3 %) were from Baan Thungchon area, while 168 were from Moo 6 and Moo 7 of Sichon district. The majority of participants were female (431, 55.7 %). The mean age of the participants was 79 ± 9.1 years, with a minimum age of 60, and a maximum age of 95. Their comorbidities were hypertension (42.9 %), type II diabetic mellitus (33.2 %), dyslipidemia (37.5 %), and osteoarthritis of the knees (35.8 %). 35.1 % of them also had positive TUGT. Sixty-seven participants (8.7 %) scored 7 or lower in the Abbreviated Mental Test (AMT). Five participants (7.5 %) had a positive screening for dementia.